Demokracja bezpośrednia w Unii Europejskiej (ze szczególnym uwzględnieniem Traktatu Konstytucyjnego Unii Europejskiej) - Kużalewska, Elżbieta (Przegląd Politologiczny, 2018)
The literature on the subject expresses the uniform opinion that direct democracy increases citizens’ interest in political matters, and that a referendum on broadly understood European integration transfers the European debate to the level of a national political discussion conducted not only by politicians, but primarily by citizens. It seems a reasonable solution, then to bring European citizens closer to making decisions by means of referenda. Recently referenda have clearly gained in importance, as evidenced by the growing number of votes cast by citizens. Western literature has named this phenomenon ‘referendomania.’ The ruling elite appealing to citizens to express their standpoint on matters of broadly understood European integration can be perceived as a certain form of evolution of the EU’s political system, where particular emphasis is placed on the involvement of common people.